Dynamic analysis of rail track for high speed trains: 2D approach - Correia, A. Gomes (2007)
In the framework of an ongoing national research project involving the University of Minho, the National Laboratory of Civil Engineering and the New University of Lisbon, different commercial FEM codes (DIANA, PLAXIS and ANSYS) were tested to model the dynamic performance of a high speed train track. Initially a plain strain model is considered in a robin test using experimental data from a well documented instrumented standard ballast rail track under the passage of a HST at 314 km/h. Numerically predicted results are presented and assessed, and comparison is made between the different codes and also the experimental data.